Culture, Technology and the Image Techniques of Engaging with Visual Culture - Pilcher, Jeremy (2023)
class Culture, Technology and the Image explores the technologies deployed when images are archived, accessed and distributed. The chapters discuss the ways in which habits and techniques used in learning and communicating knowledge about images are affected by technological developments. The volume discusses a wide range of issues, including access and participation; research, pedagogy and teaching; curation and documentation; circulation and re-use; and conservation and preservation. The book illustrates how knowledge about images is intertwined with the methods that are used to store, retrieve and analyse those images and the information associated with them. Focusing on the implications of technology for processes and practices brings into view the permeable nature of boundaries between such disciplines as art history, media studies, museum studies and archiving. As such, this text will appeal to a broad academic audience, including art historians interested in the digital; media studies scholars; digital humanities scholars interested in expanding beyond textual scholarship; as well as new students in any of these fields.